Efficacy of Cladribine Tablets in high disease activity subgroups of patients with relapsing multiple sclerosis: A post hoc analysis of the CLARITY study. (May 2019) - Giovannoni, Gavin; Soelberg Sorensen, Per; Cook, Stuart; Rammohan, Kottil W; Rieckmann, Peter; Comi, Giancarlo; Dangond, Fernando; Hicking, Christine; Vermersch, Patrick
Background: In the CLARITY (CLAdRIbine Tablets treating multiple sclerosis orallY) study, Cladribine Tablets significantly improved clinical and magnetic resonance imaging (MRI) outcomes (vs placebo) in patients with relapsing-remitting multiple sclerosis. Objective: Describe two clinically relevant definitions for patients with high disease activity (HDA) at baseline of the CLARITY study (utility verified in patients receiving placebo) and assess the treatment effects of Cladribine Tablets 3.5 mg/kg compared with the overall study population. Methods: Outcomes of patients randomised to Cladribine Tablets 3.5 mg/kg or placebo were analysed for subgroups using HDA definitions based on high relapse activity (HRA; patients with ⩾2 relapses during the year prior to study entry, whether on DMD treatment or not) or HRA plus disease activity on treatment (HRA + DAT; patients with ⩾2 relapses during the year prior to study entry, whether on DMD treatment or not, PLUS patients with ⩾1 relapse during the year prior to study entry while on therapy with other DMDs and ⩾1 T1 Gd+ or ⩾9 T2 lesions). Results: In the overall population, Cladribine Tablets 3.5 mg/kg reduced the risk of 6-month-confirmed Expanded Disability Status Scale (EDSS) worsening by 47% vs placebo. A risk reduction of 82% vs placebo was seen in both the HRA and HRA + DAT subgroups (vs 19% for non-HRA and 18% for non-HRA + DAT), indicating greater responsiveness to Cladribine Tablets 3.5 mg/kg in patients with HDA. There were consistent results for other efficacy endpoints. The safety profile in HDA patients was consistent with the overall CLARITY population. Conclusion: Patients with HDA showed clinical and MRI responses to Cladribine Tablets 3.5 mg/kg that were generally better than, or at least comparable with, the outcomes seen in the overall CLARITY population.